2021
DOI: 10.18332/tpc/134561
|View full text |Cite
|
Sign up to set email alerts
|

Association of health warning labels and motivation to quit waterpipe tobacco smoking among university students in the Eastern Mediterranean Region

Abstract: INTRODUCTION This study aimed to determine associations between health warning label content and motivation to quit waterpipe smoking by gender and smoking location. METHODS Convenience samples of university students in three Eastern Mediterranean countries -Egypt (n=442), Jordan (n=535) and Palestine (n=487) -completed an online survey assessing health warning labels. Multinomial logit regression models were conducted to determine the association between different variables, particularly gender and smoking l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This high dependence rate carries significant implications for health policy. Like cigarette tobacco policies, policies addressing WPS should be introduced with robust measures aimed at behavioral change, including smoking-free legislation and health warning labeling [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This high dependence rate carries significant implications for health policy. Like cigarette tobacco policies, policies addressing WPS should be introduced with robust measures aimed at behavioral change, including smoking-free legislation and health warning labeling [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent qualitative Jordanian study showed that a HWL displaying a child in distress was the most recalled within a set of 10 HWLs [45]. Another study among university students in three countries (Jordan, Egypt, and Palestine) showed that HWLs related to protecting children from exposure to WP smoke ("Protect your children: Don't let them be exposed to WP smoke") was the most effective in motivating WP users to quit [46]. This research emphasizes using HWLs with children's pictures to target users in Arab countries in the EMR.…”
Section: Discussionmentioning
confidence: 99%
“…We grouped countries into four categories. Although category 1 includes countries that clearly defined waterpipe as part of their tobacco product definition and thus, in principle, regulate it in other policy parts, in line with the FCTC articles, we cannot make conclusions as to the strength of those policies without looking more carefully at the nature of the regulation and the extent to which it addressed the uniqueness of WTS 11 12. For example, although 73% of the countries in category 1 address Article 11, it is unclear if their guidance is tailored to WT.…”
Section: Discussionmentioning
confidence: 99%
“…The guiding document for global tobacco control regulation is the Framework Convention on Tobacco Control (FCTC), the world’s first global health treaty, which includes evidence-based policy recommendations translated through required ‘articles’. Research evidence and reports from the Conference of the Parties (COP) to the FCTC on global regulatory practices have documented potentially effective regulatory practices for WTS,11–14 such as using waterpipe-specific health warning labels. As a result, global health guidance is emerging on WTS-specific policies 15–18…”
Section: Introductionmentioning
confidence: 99%